Improvement on efficiencies of water electrolyzer using packed-bed electrodes. (29th June 2016) - Shau, Abhra; De, P.; Ray, P.
Abstract: In the present work, efforts have been made to increase the efficiency for electrolytic production of hydrogen from dilute acidic/alkaline water by increasing the surface area of electrodes using novel packed-bed electrodes instead of conventional plate electrodes. While aqueous 20–30% (w/v) KOH solution is normally used commercially, the feasibility of using dilute solutions has been studied. Acidic medium has been found to be unsuitable due to rapid corrosion and low current efficiency. In alkaline media, packed-bed electrodes have been found to exhibit better current and energy efficiencies compared to plate electrodes. Interestingly, solid packings exhibited higher efficiencies than hollow packings even though hollow packings have 25% greater surface area. Oxidation of electrode materials seems to be partially responsible for this drop in efficiency. Entrapment of produced gases inside the hollow packings may also play an important role. Highlights: Novel packed bed electrodes increase current efficiencies in water electrolysis. Higher current efficiency ≈97% achieved with 0.50% KOH than 20–30% KOH. Energy efficiency of about 50% achieved using 0.50% KOH. Undesired reactions at electrodes confirmed by XRD, EDAX, AAS analysis.